The occurrence of alien species in the settlement areas of the Kampinos National Park and its vicinity (Central Poland) - Kirpluk, Izabella; Bomanowska, Anna (Biodiversity: Research and Conservation, 2015)
Studies aimed at the identification of the range and method of spread of alien plant species in settlement areas in Kampinos National Park (KNP) and its immediate vicinity were carried out in years 2012-2014. Special emphasis was put on surveying the sites of invasive alien species (IAS), and diagnosing potential threats posed to the natural and semi-natural vegetation of the national park by the IAS present in rural areas. We found 53 alien vascular plant species, including 40 invasive taxa which may potentially pose a threat to the ecosystems of KNP. Species encroaching from settlement areas to semi-natural and natural communities included: Bidens frondosa, Echinocystis lobata, Impatiens glandulifera, I. parviflora, Juncus tenuis, Lupinus polyphyllus, Reunoutria japonica and Solidago gigantea. Most of them were species from the highest invasiveness (IV and III) classes in Poland. Similarity analysis carried out for all investigated localities with regard to all alien species, and only for invasive ones showed a clear division into separate groups: villages within the boundaries of the national park and villages outside the park.